Energy-filtered transmission electron microscopy of ferritin. - Shuman, H (1982)
The focusing properties of a magnetic-sector spectrometer are shown to be suitable for forming high-spatial-resolution, energy-filtered transmission electron microscope images. Filtered images of ferritin molecules by using electrons scattered from the characteristic iron M2,3 and carbon K absorption edges clearly distinguish the 75-A iron core and 120-A protein shell. The minimum detectable mass is estimated to be 0.84 X 10(-20) g for Fe for an electron dose of 18 C/cm2 and 99% confidence.